AN OVERVIEW OF TPE-POLYAMIDE BLEND OPTIMIZATION FOR OVERMOLDING TECHNIQUES - Ihab S. Hasan; Emad Q. Hussein; Fadel Hassan Abdul Hussein (Journal Park Publishing, 2023)
Polyamides (PA) and thermoplastic elastomers (TPE) are foundational polymers, each boasting distinct characteristics. However, their intrinsic incompatibility presents challenges when blending them, particularly in overmolding processes. This review delves into the innovative strategies and interventions explored to improve TPE-PA adhesion, emphasizing the role of reactive molecules such as maleic anhydride and glycidyl methacrylate as potential compatibilizers. Through a comprehensive analysis of various studies, the influence of these compatibilizers, the reaction dynamics, and the resultant mechanical properties of the blends are elucidated. Additionally, the criticality of factors like interfacial temperature in overmolding processes is underscored. The findings provide insights into optimizing TPE-PA blends, unlocking the potential for superior, toughened materials with enhanced applicability in various industries.
Keywords: TPE-Polyamide Blends, Overmolding Challenges, Compatibilizer Strategies, Reactive Molecule Adhesion, Interfacial Temperature Optimization.